Purchasing Power Profile: 35th and North - (:unkn) unknown (My University, 2001)
To help identify the economic assets of central city neighborhoods and to further employment opportunities for city residents the University of Wisconsin-Milwaukee Employment and Training Institute prepared state-of-the-art purchasing power estimates of consumer expenditures and retail sales leakage/surplus by neighborhood. The ETI drill downs were designed to help determine the diversity of the workforce and to further economic development for underserved communities and for neighborhoods with concentrations of residents of color. This presentation describes the purchasing power assets within three miles of 35th Street and North Avenue, a predominantly African American community on Milwaukee’s north side.
Keywords: foreclosures; predatory lending; subprime lending; morgages